Method for TDOA localisation in over-the-horizon environments - Jian-Xin Liu; Xing-Peng Mao (The Journal of Engineering, 2019)
Here, the authors propose a new over-the-horizon time-difference-of-arrival localisation model based on the ground-wave and simultaneously put forward a modified semi-definite programming algorithm, which is called Ground-wave semi-definite programming (G-SDP). If both the target and the base stations are on the surface of the earth and far away from each other, the propagation path of the signal is a curve along the surface instead of a straight line, thus making the traditional positioning model inefficient. To overcome the problem, they develop a novel localisation model and explore a priori information to achieve improvements on SDP algorithms. An iteration trick is also utilised to obtain better performance when the signal-to-noise ratio is low. The simulation results show the merits of the improved model and G-SDP.